2021
DOI: 10.1183/13993003.02269-2019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in patients with pulmonary Mycobacterium avium complex disease

Abstract: RationaleNontuberculous mycobacteria (NTM) are environmental mycobacteria that can cause a chronic progressive lung disease. Although epidemiological data indicate potential genetic predisposition, its nature remains unclear.ObjectivesWe aimed to identify host susceptibility loci for Mycobacterium avium complex (MAC), the most common NTM pathogen.MethodsThis genome-wide association study (GWAS) was conducted in Japanese patients with pulmonary MAC and healthy controls, followed by genotyping of candidate singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Human genetic backgrounds influence susceptibility to and/or severity of infectious diseases. Genome-wide association studies (GWAS) have identified a number of genetic loci associated with infectious diseases, including class I human leukocyte antigen (HLA) and CCR5 implicated in HIV infection, 18q11 in tuberculosis, HBB in malaria infection, and 16p21 in Mycobacterium avium complex (MAC) [8][9][10][11] . Thus, human host genetics is expected to define the susceptibility to COVID-19 and explain the populational differences in disease mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Human genetic backgrounds influence susceptibility to and/or severity of infectious diseases. Genome-wide association studies (GWAS) have identified a number of genetic loci associated with infectious diseases, including class I human leukocyte antigen (HLA) and CCR5 implicated in HIV infection, 18q11 in tuberculosis, HBB in malaria infection, and 16p21 in Mycobacterium avium complex (MAC) [8][9][10][11] . Thus, human host genetics is expected to define the susceptibility to COVID-19 and explain the populational differences in disease mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a clinical study revealed a decrease in the estrogen level 21 and a genome-wide association study revealed a single nucleotide polymorphism pattern in the chromosomal region encoding the calcineurin-like DF-hand protein 2 (CHP2) 22 . These ndings may provide insight into the mechanism of persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we were unable to detect T-cell responses against MAC-specific peptides or increased reactivity compared to IGRA+HC against Mav lysate in multiple antigen-specific assays. (45)(46)(47). Further studies will be needed to assess the impact of both macrophage hyperreactivity and relative T-cell deficiency in Mav pathogenesis.…”
Section: Discussionmentioning
confidence: 99%